Status of thyroid profile in Type-2 diabetes mellitis - Yadav, Shekhar Chandra; Saldhana, Alwin; Majumdar, Biswajit (Journal of Nobel Medical College, 2012)
Diabetes mellitus is a group of metabolic disorder characterized by hyperglycemia resulting from defect in insulin secretion and/or insulin action. Thyroid dysfunction in diabetes mellitus patient has been frequently encountered. The clinical relationship between diabetes mellitus and thyroid function is becoming more widely recognized with hypothyroidism among diabetes mellitus patient. Total of 100 cases and 50 controls are enrolled into the study. Their fasting venous blood sample was taken and analyzed for blood sugar, T3, T4 and TSH. Blood sugar and TSH level were elevated while T3 and T4 level were statically decreased in case group in comparison to control group.DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7302 Journal of Nobel Medical College (2012), Vol.1 No.2 p.64-71